Repair of aged bulk-fill composite with posterior composite: Effect of different surface treatments - Ayar, Muhammet Kerim; Guven, Mehmet Esad; Burduroglu, HATİCE DEFNE; BURDUROĞLU, HATİCE DEFNE; ERDEMİR, FATİH (My University, 2019)
Objective In the present study, the ability of posterior resin composite to repair aged bulk-fill resin composite and vice versa were assessed by shear bond strength testing. Materials and Methods Resin composite substrates were aged and surfaces were abraded with abrasive papers, then bulk-fill substrates were repaired with posterior resin composite and vice versa using different surface treatments (no surface treatment [control]; etching with 37% phosphoric acid [H3PO4] for 20 seconds; etching with 10% hydrofluoric acid [HF] for 20 seconds; etching with 37% H3PO4 for 20 seconds + adhesive application; etching with 10% HF for 20 seconds + adhesive application; adhesive application only). Shear bond strengths (SBS) were then measured and surface roughness values (Ra) were determined. Cohesive strengths of nonaged resin composites were measured and used as reference groups. Resin composite surfaces after acid etching were evaluated by SEM. Data were analyzed using ANOVA and Fisher-s LSD tests (P < .05). Results ANOVA showed that resin composite repair type did not affect SBS significantly (P = .850), while it showed that surface treatments significantly affected the SBS (P = .000). Only a combination of etching with 10% HF for 20 seconds with resin adhesive application provided similar SBS values with those of the positive control. Conclusions It was concluded that the aged bulk-fill resin composite would be effectively repaired with conventional posterior resin composite or vice versa if proper repair protocol was deployed. Clinical Significance The combination of 10% HF etching and adhesive application would provide efficient repair strength when the aged bulk fill resin composite is repaired with conventional posterior resin composite or vice versa.